A reassessment of the impact of trauma systems consultation on regional trauma system development. Issue 6 (June 2015) - Winchell, Robert J.; Sanddal, Nels; Ball, Jane; Michaels, Holly; Kaufmann, Christoph R.; Gupta, Rajan; Esposito, Thomas J.; Subacius, Haris
<x xml:space="preserve">Abstract</x> BACKGROUND Previous studies have shown that trauma systems decrease morbidity and mortality after injury, but progress in system development has been slow and inconsistent. This study evaluated the progress in 20 state or regional systems following a consultative visit conducted by the Trauma Systems Evaluation and Planning Committee (TSEPC) of the Committee on Trauma, expanding on a previous study published in 2008, which demonstrated significant progress in six systems following consultation. METHODS Twenty trauma systems that underwent TSEPC consultation between 2004 and 2010 were studied. Status was assessed using a set of 16 objective indicators. Baseline scores for 14 regions were calculated during the consultation visit and taken from the 2008 study for the remaining six. Postconsultation status was assessed during facilitated teleconferences. Progress was assessed by comparing changes in indicator scores. RESULTS There was significant improvement in approximately 80% of systems evaluated within 60 months following the consultation. There was no progress in five of six systems reevaluated over 80 months after consultation, and all four systems evaluated over 100 months after consultation showed erosion of progress. Significant improvements were seen in 10 of the 16 individual indicators, with the greatest gains related to system standards, data systems, performance improvement, prehospital triage criteria, and linkages with public health. Consistent with the 2008 study, the two indicators related to financing for the trauma system showed no improvement. CONCLUSION The TSEPC consultation process continues to be associated with improvements in trauma system development in approximately 80% of cases, consistent with the 2008 study, but gains are not self-sustaining. There was a stagnation in progress and a deterioration in total score over time, suggesting that a repeat consultation may be beneficial. System funding remains a challenge and was the area most likely to suffer setbacks over during study period. LEVEL OF EVIDENCE Care management study, level V.